HUBUNGAN PERSONAL HYGIENE DAN SANITASI LINGKUNGAN DENGAN KEJADIAN SKABIES DI PONDOK PESANTREN AL-KAUTSAR PEKANBARU - Desmawati ' '; Ari Pristiana Dewi; Oswati ' Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this research is to know the relationship between personal hygiene and environmental sanitation with incident of scabies of Al-Kautsar boarding school in Pekanbaru. The methodology on this research was a descriptive correlation with cross sectional approach. There are 100 participants collected by using proportionate stratified random sampling. Measuring instrument used was aquestionnairesheet consisting of personal hygiene and environmental sanitation also an observation sheet consisting of signs of scabies. In this research, we use bivariat analysis with chi square test. Basic on statistical result, p value= 0.781 (p value > 0.05) it’s did not show relationship between personal hygiene with incident of scabies, and also statistical result p value=0.306 (p value > 0.05) it’s did not show relationship between environmental sanitation with incident of scabies. This research suggest to Al-Kautsar boarding school to maintain good personal hygiene and environmental sanitation so thatstudentsavoidscabies. Keyword: personal hygiene, environmental sanitation, scabies.